Fangsheng (æ”¾ç”Ÿ) and Its Critical Discourse on Environmental Ethics in Buddhist Media - Latifah Latifah; Ary Budiyanto (International Journal of Interreligious and Intercultural Studies, 2020)
Religious views of a community group are very influential in determining their attitudes and behavior towards nature and the environment. On the one hand, there is a worldview correlation that affects attitudes that are less friendly to nature as well as human superiority among other creatures that makes it feel entitled to exploit nature. On the other hand, religious views are also a motivation for caring for and loving nature, as is the will of Buddhists to create happiness for all living things. Reflections on choosing a moderate way of life prevent greed that can cause damage to nature so that sustainable development can be realized. The media, especially digital media, represents the implementation of Buddhist environmental ethics in a variety of writing frames. This study aims to look at Fangshen (æ”¾ç”Ÿ) ritual in critical discourse on environmental ethics perspective as represented in Indonesian Buddhist media such as Buddhazine, Kompasiana, Tionghoa.info, and etcetera. This research shows that the discourse on environmental ethics in Buddhist media is at the point of intersection between natural disasters as a result of karma (kamma), paramita funds to change karma, responsibility for protecting nature, and compassion for all beings.